High levels of virological failure with major genotypic resistance mutations in HIV-1-infected children after 5 years of care according to WHO-recommended 1st-line and 2nd-line antiretroviral regimens in the Central African Republic: A cross-sectional study. Issue 10 (March 2017) - Mossoro-Kpinde, Christian Diamant; Gody, Jean-Chrysostome; Mboumba Bouassa, Ralph-Sydney; Mbitikon, Olivia; Jenabian, Mohammad-Ali; Robin, Leman; Matta, Mathieu; Zeitouni, Kamal; Longo, Jean De Dieu; Costiniuk, Cecilia; Grésenguet, Gérard; Touré Kane, Ndèye Coumba; et al.
Abstract : Abstract: A large cohort of 220 HIV-1-infected children (median [range] age: 12 [4–17] years) was cared and followed up in the Central African Republic, including 198 in 1st-line and 22 in 2nd-line antiretroviral regimens. Patients were monitored clinically and biologically for HIV-1 RNA load and drug resistance mutations (DRMs) genotyping. A total of 87 (40%) study children were virological responders and 133 (60%) nonresponders. In children with detectable viral load, the majority (129; 97%) represented a virological failure. In children receiving 1st-line regimens in virological failure for whom genotypic resistance test was available, 45% displayed viruses harboring at least 1 DRM to NNRTI or NRTI, and 26% showed at least 1 major DRM to NNRTI or NRTI; more than half of children in 1st-line regimens were resistant to 1st-generation NNRTI and 24% of the children in 1st-line regimens had a major DRMs to PI. Virological failure and selection of DRMs were both associated with poor adherence. These observations demonstrate high rate of virological failure after 3 to 5 years of 1st-line or 2nd-line antiretroviral treatment, which is generally associated with DRMs and therapeutic failure. Overall, more than half (55%) of children receiving 1st-line antiretroviral treatment for a median of 3.4 years showed virological failure and antiretroviral-resistance and thus eligible to 2nd-line treatment. Furthermore, two-third (64%) of children under 2nd-line therapy were eligible to 3rd-line regimen. Taken together, these observations point the necessity to monitor antiretroviral-treated children by plasma HIV-1 RNA load to diagnose as early as possible the therapeutic failure and operate switch to a new therapeutic line.